2021
DOI: 10.5964/jspp.7077
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the manifestations of neoliberalism in academia: Academic collective action in Turkey

Abstract: Academic Collective Action (ACA) stands as a small-scale collective action for social change toward liberation, independence and equity in academia. Academic collectives in Turkey, as an example of ACA, prefigure building academia outside the university by emphasizing the extent to which neoliberal academia has already prepared the groundwork for more recent waves of oppression. In this research, we aim to reveal the manifestations of neoliberalism in ACA as captured with prominent social/political psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Author 2 was a “petitioner” and Author 1 was a “nonpetitioner” but our common desire had been beyond an academic call for “peace.” Specifically, we were both committed to raising international voices to show that Kurds who resist against the state oppression and colonial exploitation by fighting for liberation and those who support Kurds are being violently punished in Turkey. First, we worked as a larger collective group to support each other for research and to make our voice heard hoping that the world would see the extent of state oppression (Coşkan et al, 2021; Reicher, 2017). Second and more importantly, since then, we (Authors 2 and 1) have talked more about our Kurdishness, reflexively questioning our previous studies, and our interconnectedness with the Kurdish struggle.…”
Section: Why and How Do We Do What We Do?mentioning
confidence: 99%
“…Author 2 was a “petitioner” and Author 1 was a “nonpetitioner” but our common desire had been beyond an academic call for “peace.” Specifically, we were both committed to raising international voices to show that Kurds who resist against the state oppression and colonial exploitation by fighting for liberation and those who support Kurds are being violently punished in Turkey. First, we worked as a larger collective group to support each other for research and to make our voice heard hoping that the world would see the extent of state oppression (Coşkan et al, 2021; Reicher, 2017). Second and more importantly, since then, we (Authors 2 and 1) have talked more about our Kurdishness, reflexively questioning our previous studies, and our interconnectedness with the Kurdish struggle.…”
Section: Why and How Do We Do What We Do?mentioning
confidence: 99%
“…In current neoliberal academia, however, expectations regarding the role of teachers have changed profoundly. The British audit culture that has arisen from the obsession with ‘productivity’ has been reproduced in numerous academic contexts, such as the Portuguese, Turkish and Latin American (Coşkan et al, 2021; Ferreira, 2022; Torres and Schugurensky, 2002). It has led to the implementation of a complex monitoring apparatus aimed at quantifying academic labour, which also encompasses teaching activities (Barcan, 2013; Pereira, 2017).…”
Section: Emotional Labour Versus Care In Neoliberal Academiamentioning
confidence: 99%
“…In a similar vein, Acar and Coşkan (2020) found that participation in-but not vicarious experience of-collective action resulted in empowerment, including feeling both individually and collectively efficacious and feeling a sense of support. In a similar vein, Coşkan et al (2021) noted that contextual factors such as political climate and neoliberalism could take away from feelings of empowerment-especially relevant for research on collective action in repressive climates (see Ayanian et al, 2021).…”
Section: Outcomes Of Collective Actionmentioning
confidence: 99%